1995
DOI: 10.1128/iai.63.12.4576-4583.1995
|View full text |Cite
|
Sign up to set email alerts
|

Influence of site specifically altered Mip proteins on intracellular survival of Legionella pneumophila in eukaryotic cells

Abstract: Legionella pneumophila, the causative agent of Legionnaires' disease, is able to survive intracellularly in eukaryotic cells such as monocytes, macrophages, and protozoan organisms. The Mip (macrophage infectivity potentiator) protein represents a factor of L. pneumophila necessary for optimal intracellular survival. Interestingly, Mip belongs to the substance class of FK 506-binding proteins and exhibits peptidyl-prolyl cis/trans isomerase (PPIase) activity that can be inhibited by the immunosuppressant FK 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 58 publications
1
82
0
3
Order By: Relevance
“…The purified recombinant proteins exhibited a pronounced loss of PPIase activity in in vitro peptide folding assays (5.3% for the Asp142Leu mutant and 0.6% for the Tyr185Ala mutant). However, when the same variants of mip were used to complement ⌬mip mutants, they behaved in infection studies of amoeba or human macrophages and blood monocytes as if wild-type mip had been used (243). It was concluded that either additional properties other than PPIase activity are important for Mip action during intracellular infection or the residual enzymatic activity of the mutant proteins was still sufficient for exerting PPIase-dependent phenotypes.…”
Section: Mip Of Legionella Pneumophilamentioning
confidence: 99%
“…The purified recombinant proteins exhibited a pronounced loss of PPIase activity in in vitro peptide folding assays (5.3% for the Asp142Leu mutant and 0.6% for the Tyr185Ala mutant). However, when the same variants of mip were used to complement ⌬mip mutants, they behaved in infection studies of amoeba or human macrophages and blood monocytes as if wild-type mip had been used (243). It was concluded that either additional properties other than PPIase activity are important for Mip action during intracellular infection or the residual enzymatic activity of the mutant proteins was still sufficient for exerting PPIase-dependent phenotypes.…”
Section: Mip Of Legionella Pneumophilamentioning
confidence: 99%
“…Within this ecological niche, L. pneumophila alters its gene expression and expresses various virulence-related genes in response to starvation and signalling by (p)ppGpp (Abu Kwaik et al, 1998). The Mip (macrophage infectivity potentiator) protein, which belongs to the substance class of FK 506-binding proteins and exhibits peptidyl-prolyl cis/trans isomerase, represents a factor of L. pneumophila necessary for optimal intracellular survival (Wintermeyer et al, 1995). L. pneumophila is able to replicate within the phagosomes of mammalian cells, because it is not traf®cked through the endosomal±lysosomal pathway and is surrounded by the rough endoplasmic reticulum (Abu Kwaik et al, 1998).…”
Section: Protozoa and Pathology Of Legionellosismentioning
confidence: 99%
“…The expression of a number of specific virulence traits could be linked to the particular growth phases (for review see Heuner and Steinert, 2003). Among these is the Legionella Mip (macrophage infectivity potentiator) protein which is known to contribute to the survival of Legionella in different cell lines and to virulence in guinea pigs (Engleberg et al, 1989;Cianciotto et al, 1990;Cianciotto and Fields, 1992;Wintermeyer et al, 1995;Swanson and Hammer, 2000). The Mip promoter is temporarily repressed immediately after invasion of human monocytes and regains activity after 24 h of intracellular replication (Wieland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The fold of the C-terminal domain (residues 100-213) is closely related to the human FK506-binding protein FKBP12 (Fischer et al, 1984;Schmid, 1993). The binding of the immunosuppressants FK506 and rapamycin to a hydrophobic site of this C-terminal domain inhibit the PPIase activity of the Mip protein. Infection studies in Acanthamoeba castellanii, Hartmannella vermiformis, human mononuclear phagocytes, lung epithelial cells and guinea pigs revealed that Mip-negative mutants of Legionella are less infective when compared with their isogenic Mip-positive parental strains (Cianciotto and Fields, 1992;Cianciotto et al, 1995;Wintermeyer et al, 1995). The determination of the three-dimensional structure of Legionella Mip enabled a rational starting point for functional analysis of this protein (Köhler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%